Transfusion-related acute lung injury induced by anti-human leukocyte antigen antibodies in the donor blood – A case report (Indian Journal of Case Reports, 2025)
Transfusion-related acute lung injury (TRALI) is one of the leading causes of transfusion-related fatalities, and there are no available specific therapies. The pathophysiology of the condition is not straightforward and is poorly understood. A 2-hit model is generally attributed to underlie TRALI. In this case report, we report a case of a 72-year-old male patient with no significant history, who was transfused with packed red blood cells and developed TRALI as a consequence. He recovered in 24 h and had no sequelae. Laboratory investigations of the blood donors revealed a positive human leukocyte antigen antibody screen. Further research is required to comprehend and elucidate the pathophysiology of TRALI, for better diagnostics and therapeutic approaches for the same in the future.